Granulation and calcination of alum sludge for the development of a phosphorus adsorbent: From lab scale to pilot scale. (1st February 2021) - Everaert, Maarten; Bergmans, Jef; Broos, Kris; Hermans, Benjamin; Michielsen, Bart
Abstract: Alum sludge, an Al-oxyhydroxide rich waste product from water treatment practices, has the potential to be valorized as a P adsorbent material. However, several challenges currently prevent its application as an adsorbent in industrial setting, i.e. a limited P adsorption capacity due to saturation by organic matter and a fine nature resulting in percolation problems in adsorption bed setups. In this study, granulation and subsequent calcination of alum sludge were proposed to overcome these issues and to improve the P adsorption properties of alum-based adsorbent (ABA) materials. The effect of calcination temperature on the physicochemical properties of granular material was examined using X-ray diffraction, mass-spectroscopy coupled thermogravimetric analysis, Fourier-transform infrared spectrometry and specific surface area analysis, combined with density and crushing strength measurements. The ABA material obtained at 550 °C showed superior P adsorption properties and, therefore, this material was selected for further P adsorption testing and characterization (scanning electron microscopy and sieving). Batch P adsorption tests showed that this material had a maximum P adsorption capacity of 7.27 mg-P g −1 . Kinetic adsorption tests determined the effect of the solid-to-liquid ratio and the granule particle size on the P removal. Finally, the performance of the ABA-550 material was tested in a pilot-scale adsorption setup, using a surface water stream (0.47 mg-P L −1 ) at a flow rate of 200 L h −1 . During the test, the P removal efficiency always exceeded 86%, while the material maintained its structural stability. The results of this study illustrate the potential of granulated/calcined ABA materials for P adsorption, paving the way for the industrial application of this novel, sustainable P removal technology. Graphical abstract: Image 1 Highlights: Development of alum-based P adsorbents (ABA) via calcination of sludge granules. Calcination at 550 °C resulted in higher P uptake than at 100 °C or 300 °C. Granules calcined at 550 °C (ABA-550) showed a P adsorption capacity of 7.3 mg g −1 . Clear effects of solid:liquid ratio and particle size on ABA-550 adsorption kinetics. In a pilot-scale test, the P removal efficiency with ABA-550 was between 86% and 100%.